Development of Ethical Leadership Indicators for School Principals Under Bangkok Metropolitan Administration - Kongtoei, Khamporn; Chamnan, Samoot; Pruettikul, Sataporn (Academic Journal of Thailand National Sports University, 2018)
The purpose of this quantitative research were to study the factors and develop ethical leadership indicators of school principals under Bangkok Metropolitan Administration and to validate the measurement model of ethical leadership behavior indicator school principals under Bangkok Metropolitan Administration. The samples consisted of 500 teachers in school under Bangkok Metropolitan Administration by using a multi-stage random sampling technique. The instruments uses for collecting the data was a questionnaire, They were validated in terms of content validity by the qualified panels. The data were analyzed by arithmetic mean, Standard deviation, and confirmatory factor analysis by SPSS for Windows and LISREL. The summary of the findings were as follows: 1. Ethical leadership for school principals under Bangkok Metropolitan Administration consisted of 5 factors: they were 1) Trust 2) Fairness 3) Respect 4) Responsibility and 5) Honestly. 2. Ethical leadership for school principals under Bangkok Metropolitan Administration consisted of 5 factors with 16 indicators they were: 1) three indicators of trust; 1.1) integrity, 1.2) loyalty, and 1.3) self-respect 2) three indicators of fairness; 2.1) procedure of decision making, 2.2) fair of decision making, and 2.3) right of decision making 3) three indicators of respect; 3.1) be honor, 3.2) be polite, and 3.3) accept others 4) three indicators of responsibility; 4.1) accountability, 4.2) self-control, and 4.3) attempt to the excellent 5) four indicators of honestly; 5.1) openness of information, 5.2) transparency, 5.3) sincere and 5.4) no cheating person. 3. The result of the structural model of ethical leadership for school principals under Bangkok Metropolitan Administration fitted with empirical data.(factor loading. 81 to .92, Cronbach’s .86 to .94 and AVE .68 to .80)